Peranan Amil Sebagai Pengelola Zakat untuk Kesejahteraan Umat di Kota Bima - Hamidy Thalib; M. Irwan; Ihsan Ro’is (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2016)
This study aims to determine how to manage your Amil Zakat in Bima, knowing the role as manager Amil Zakat in the welfare of the people in the town of Bima. This study uses qualitative descriptive type of field research (field research). Our research found that the way to manage amil zakat that is there in accordance with the principle of prophethood and is not in accordance with the principle of prophethood. While his role as a manager for the welfare of the people is not yet too by looking at the maximum utilization of Zakat funds. Where pendayagunaannya more geared to consumer goods while the productive nature of the very few.